Differing responses of functional and taxonomic waterbird diversity to vegetation height and water level variation in a coastal wetland - Secondi, Jean; Percel, Gwendoline; Arzel, Céline; Davranche, Aurélie; Farau, Sébastien (Springer Nature, 2026)
The conservation of wetland biodiversity is a major global issue. In anthropogenic landscapes, it requires the identification of environmental conditions and management practices that sustainably maintain the diversity of the communities. We carried out a six-year survey over 18 sites (78 ha) in the Marais Breton, lowland grazing marshes on the western coast of Europe in France. We tested the influence of the spatio-temporal dynamic of vegetation heights, water depth and the proportion of flooded areas on the taxonomic and functional diversity of wading birds and ducks at the site scale. Taxonomic diversity was enhanced by higher spatial heterogeneity of water level and reduced by higher spatial heterogeneity of vegetation height. In sharp contrast, functional diversity was not influenced by spatial heterogeneity of water level and increased with spatial heterogeneity of vegetation height. Additionally, the effect of the spatio-temporal heterogeneity of water level and vegetation height was guild-dependent. Based on our results we encourage a management at the landscape scale integrating multiple land ownerships to promote a taxonomic and functional diversity rather than at the site scale only.